2021
DOI: 10.1080/21505594.2021.2021630
|View full text |Cite
|
Sign up to set email alerts
|

The endoplasmic reticulum stress-mediated unfolded protein response protects against infection of goat endometrial epithelial cells byTrueperella pyogenesvia autophagy

Abstract: Trueperella pyogenes is an important bacterial pathogen of a wide range of domestic and wild animals. Autophagy plays a key role in eliminating T. pyogenes in a process that is dependent on mechanistic target of rapamycin (mTOR). The endoplasmic reticulum (ER) stress response also is critical for autophagy regulation. However, the relationship between ER stress and T. pyogenes is uncharacterized and the intracellular survival mechanisms of T.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…The results showed that MEHP exposure could increase the level of intracellular Ca 2+ . Moreover, the expression level of chaperone protein GRP78 increased, indicating the dissociation of GRP78 from PERK and IRE1α molecules 38 . After separation from GRP78, phosphorylation of PERK and IRE1α occurs, then activates a series of downstream molecular reactions 39 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results showed that MEHP exposure could increase the level of intracellular Ca 2+ . Moreover, the expression level of chaperone protein GRP78 increased, indicating the dissociation of GRP78 from PERK and IRE1α molecules 38 . After separation from GRP78, phosphorylation of PERK and IRE1α occurs, then activates a series of downstream molecular reactions 39 .…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the expression level of chaperone protein GRP78 increased, indicating the dissociation of GRP78 from PERK and IRE1α molecules. 38 After separation from GRP78, phosphorylation of PERK and IRE1α occurs, then activates a series of downstream molecular reactions. 39 Our results showed that the expression of p-PERK and p-IRE1α were significantly increased after MEHP exposure.…”
Section: Discussionmentioning
confidence: 99%
“…BMMSC-exo and its target pathways have been explored extensively. Advanced glycation end products (AGEs) [108][109][110], formed by non-enzymatic reaction of reducing sugars with free amino groups of macromolecules, leads to ER stress, thus activating the unfolded protein response (UPR) [111,112]. Furthermore, UPR could initiate the C/EBP homologous protein, which is a responsible protein that modulates and induces cell apoptosis.…”
Section: Exosome Derived From Bone Marrow Mesenchymal Stem Cellsmentioning
confidence: 99%
“…However, the effects of antifungal agents on the autophagic activity in C. albicans biofilms remain unknown. Autophagy is an essential process through which damaged organelles from cytoplasm are recycled to sustain the development of organisms [ 16 , 17 ], and it is more generally classified as a basic cell survival mechanism against environmental stressors [ 18 ]. The autophagic activity of eukaryotic cells can be analyzed through alkaline phosphatase (ALP) activity, reactive oxygen species (ROS) level, and the expressions of autophagy-related genes and proteins [ 15 ].…”
Section: Introductionmentioning
confidence: 99%